Efficacy and safety of olorinab, a full agonist of the cannabinoid receptor 2, for the treatment of abdominal pain in patients with irritable bowel syndrome: Results from a phase 2b randomized placebo‐controlled trial (CAPTIVATE). Issue 5 (5th February 2023) - Chang, Lin; Cash, Brooks D.; Lembo, Anthony; Kunkel, David C.; English, Brett A.; Lindstrom, Beatriz; Gu, Guibao; Skare, Sharon; Gilder, Kye; Turner, Stewart; Cataldi, Fabio; Lipkis, Donald; et al.
Abstract: Background: Olorinab is a highly selective, peripherally acting, full agonist of cannabinoid receptor 2. This study assessed the efficacy and safety of olorinab to treat abdominal pain in patients with irritable bowel syndrome with diarrhea (IBS‐D) and constipation (IBS‐C). Methods: CAPTIVATE was a phase 2b, randomized, double‐blind, placebo‐controlled, parallel‐group trial. Eligible participants aged 18–70 years with IBS‐C and IBS‐D diagnosed per Rome IV received olorinab 10 mg, 25 mg, or 50 mg three times daily (TID) or placebo TID for 12 weeks. The primary endpoint was the change in patient‐reported average abdominal pain score (AAPS) from baseline to Week 12. Key Results: A total of 273 participants were randomized to receive olorinab 10 mg ( n = 67), olorinab 25 mg ( n = 67), olorinab 50 mg ( n = 69), or placebo ( n = 70). Although a treatment response was observed across all groups, the weekly change in average AAPS from baseline to Week 12 was not significantly different between placebo and any olorinab dose. In a prespecified subgroup analysis of participants with a baseline AAPS ≥6.5, olorinab 50 mg ( n = 35) significantly improved AAPS compared with placebo ( n = 30) ( p = 0.014). Adverse event rates were comparable between olorinab and placebo and there were no reported serious adverse events or deaths. Conclusion and Inferences: Although olorinab was well‐tolerated and improved weekly AAPS, the primary endpoint was not met. However, in participants with moderate‐to‐severe pain at baseline (AAPS ≥6.5), olorinab 50 mg significantly improved weekly AAPS compared with placebo. ClinicalTrials.gov : NCT04043455. Abstract : Patients with irritable bowel syndrome with diarrhea/constipation were randomized to olorinab or placebo. Although the primary endpoint of change in average abdominal pain score from baseline to Week 12 was not met for any olorinab dose, olorinab 50 mg significantly improved pain score in participants with moderate‐to‐severe pain at baseline.